PENERAPAN MEDIA VIDEO ANIMASI DAN GOOGLE SITES UNTUK MENINGKATKAN HASIL BELAJAR POLINOMIAL KELAS XI MIPA 2 SMA NEGERI 1 PALU - I Wayan Bayu Rasdana; Muh. Rizal; Wiwik Astuti (Program Studi Pendidikan Matematika FKIP Universitas Islam Darul Ulum, 2023)
This research aims to determine the implementation of animated video media and Google Sites to improve learning outcomes in polynomials. The type of research used is classroom action research. This research design refers to Arikunto's research design, which consists of planning, implementation, observation, and reflection. The subjects in this study were all students of class XI MIPA 2 at SMA Negeri 1 Palu, totaling 35 people. The research was conducted in two cycles. The research results showed that (1) There was an increase in individual student mastery from in the first cycle to in the second cycle. (2) There was an increase in classical student mastery from 71.4% in the first cycle to 88.5% in the second cycle. (3) The teacher and student activities in each activity were categorized as good and very good. (4) The students' response showed that learning through the implementation of video media and Google Sites, namely, animated video media, made the students interested in learning and facilitated their understanding of the given problems. Google Sites reduced the use of mobile phones for non-learning-related matters, and it also facilitated students in searching for references and information. Based on the researcher's findings, it is recommended that educators implement animated video media and Google Sites in relevant subjects.